Family caregivers' experience of care with a child with cerebral palsy: the lived experiences and challenges of caregivers in a resource-limited setting in northern Ghana - Joseph Ngmenesegre Suglo; Mavis Mallory Mwinbam; Yaa Nyarko Agyeman; Margaret Wekem Kukeba (BMJ Publishing Group, 2023)
Introduction Caring for a child with cerebral palsy may be more emotionally and physically exhausting than caring for a typical growing child. The family caregivers' perspective of this phenomenon needs exploring to facilitate the development of services. Our study explored the challenges family caregivers face with children with cerebral palsy in a resource-limited context in northern Ghana.Methods We conducted a qualitative study underpinned by phenomenological principles where it is believed that the reality of a phenomenon is tied to caregivers' perspectives of their own experiences. In this study, we unearthed caregivers' experiences/challenges from their own perspectives. The method of data analysis used was to allow the issues to emerge from the data (inductive process) using the content analysis approach. We recruited 13 caregivers of children with cerebral palsy from the physiotherapy unit at Tamale Teaching Hospital, and conducted individual in-depth interviews supported by an open-ended topic guide. Interviews were audio recorded, transcribed, and translated and coded inductively before conducting a content analysis of the data when grouped into themes.Results We have identified barriers to managing a child with cerebral palsy, including sociocultural barriers (values, attitudes and belief systems within society), economic challenges and immediate physical care burdens. Specific barriers included discrimination and isolation, lack of family and societal support, with poor access to health information and formal education. Others were lack of information on the cause and course of cerebral palsy, caregivers' loss of jobs, increased healthcare expenditure and struggles in lifting and moving children, which resonate with evidence-based multidimensional model of caregiving process and caregiver burden.Conclusion Caregivers have the arduous task of caring for a child with cerebral palsy. Social support interventions and policy initiatives that seek to ameliorate caregivers' finances and make formal education accessible to this marginalised child population may be beneficial in this context.